Macroeconomic conditions, financial constraints, and firms’ financing decisions - Chang, Xin; Chen, Yunling; Dasgupta, Sudipto (Journal of Banking & Finance, 2019)
We examine how time-varying macroeconomic conditions affect firms’ financing decisions. A principal components decomposition of several macroeconomic variables characterizes three phases of the business cycle relative to recessions: early recovery, robust recovery, and economic crest; a fourth represents “windows of opportunity” in capital markets that are unrelated to recessions. This characterization yields results that traditional approaches miss. Specifically, debt issuance exhibits a non-monotonic pattern during the upward phase of the business cycle: it declines in robust recovery relative to recessions but peaks at the economic crest. Financially constrained firms issue more equity during windows of high stock market valuation, whereas unconstrained firms time debt issuance in response to debt market spreads.